Cold surges and dust events: Establishing the link between the East Asian Winter Monsoon and the Chinese loess record. (1st October 2016) - Wyrwoll, Karl-Heinz; Wei, Junhong; Lin, Zhaohui; Shao, Yaping; He, Feng
Abstract: The Chinese loess/palaeosol succession is one of the most comprehensive and intensively studied archives of Neogene and Quaternary global palaeoclimate events. Its stratigraphic details are widely recognised to indicate close links to the history and function of the East Asian Winter Monsoon (EAWM) – one of the most active components of the Earth's climate system. But the formal meteorological links between the EAWM and dust emission, both in the present day and in the past, have not been established and with it, the veracity of the loess record as an indicator of the EAWM questioned. Here we show that present day major dust events over northern China, while largely occurring during spring, are nevertheless 'conditioned' by the strength of the preceding EAWM. We also demonstrate, for the first time, a close link between the occurrence of dust events and the strength of the EAWM. From these findings, linked to global-scale climate model simulations, we conclude that the Chinese loess succession provides a convincing proxy record of the strength of the East Asian Winter Monsoon. Highlights: The Chinese loess/palaeosol succession presents a comprehensive archive of Neogene and Quaternary global palaeoclimate events. The succession is linked to the strength of the East Asian Winter Monsoon, an inference that has been recently challenged. We show that present day major dust events are 'conditioned' by the strength of the preceding winter monsoon. Palaeoclimate model simulations indicate a progressive weakening of the winter monsoon over the last c. 21, 000 years. We confirm that the Chinese loess succession provides a proxy record of the strength of the East Asian Winter Monsoon.